Global Research Trends on Immersive Technology in Education: A Bibliometric Analysis (2007-2025) - Ahmad Susilo; Irwanto Irwanto; Ucu Cahyana (Universitas Muhammadiyah Surabaya, 2026)
The rapid advancement of science and technology has accelerated the integration of immersive technologies, including virtual reality (VR), augmented reality (AR), and mixed reality (MR), into educational practices. Although research on immersive learning has grown substantially, a comprehensive bibliometric mapping that systematically reveals global research trends, intellectual structures, and emerging directions remains limited. This study addresses this gap by providing an up-to-date bibliometric overview of immersive educational technology research. Data were retrieved from the Scopus database for publications published between 2007 and 2025. An initial search identified 1,849 records, which were screened using predefined inclusion and exclusion criteria, resulting in 618 publications for analysis. Bibliometric analysis was conducted using VOSviewer and Biblioshiny (R package) to examine publication growth, keyword co-occurrence, citation performance, co-authorship networks, leading journals, influential authors, institutions, and country contributions. The results indicate a substantial increase in research output, with publication activity peaking in 2024 (177 publications). The dominant research themes were virtual reality, immersive learning, and augmented reality, reflecting a strong emphasis on technology-enhanced learning environments. The most productive publication outlets were Education and Information Technologies, Journal of Chemical Education, and Frontiers in Education. This study contributes a comprehensive bibliometric mapping of immersive educational technology by integrating multiple bibliometric indicators to identify research hotspots, collaboration patterns, and emerging trends. The findings provide valuable evidence for researchers, educators, and policymakers in identifying future research opportunities and supporting the effective integration of immersive technologies into education.